Heritage and culture in the evolution of the night time city - the case of Lisbon - Moreira, Maria da Graça (AESOP, 2016)
Urban planning is elaborated considering mainly the daily activities of the city or at least those who work 24 hours. The leisure night activities , who can be in some cities an important economic and touristic factor, are in general forgot. May be because there dynamic is very fast in comparison with traditional planning time. Local or regional culture determines the way of appropriation of the urban space by a specific population and presents great variations mainly in the nightly use of public space. Industrial heritage has been, in the last decades, an important element of expansion of the nightly leisure activities by the rehabilitation and / or re-use of the buildings. This research studies the evolution of the centrality, considering the culture and the built heritage of the city as a function of a set of activities that happen during a period that elapses after dinner time. When it is studied the night time period, must considered that it varies along the year for a given place, at medium latitudes. Therefore in this work it is defined as the analyzed period, the one that is bounded by diner time and the first ours of the following day. The evolution of the use of night time, in different activities, depends on the availability of energy so that these activities may work, namely the technologic evolution related to lighting, as well as the one related to comfort, available in closed spaces but nowadays, as well, in open spaces.
Proceedings of the IV World Planning Schools Congress, July 3-8th, 2016 : Global crisis, planning and challenges to spatial justice in the north and in the south